Soil reinforcement with geotextiles - Jewell, R. A. (CIRIA special publication, 1996)
A design manual on geotextiles and related products which are providing new and cost-effective ways to design and construct earth structures and to repair the slopes of older ones. This publication is a source of guidance for geotechnical, structural and highway engineers amongst others.